IMPROVING THE QUALITY OF SPAM DETECTION OF COMMENTS USING SENTIMENT ANALYSIS WITH MACHINE LEARNING (Computer systems and information technologies, 2023)
Nowadays, people spend more and more time on the Internet and visit various sites. Many of these sites have comments to help people make decisions. For example, many visitors of an online store check a product’s reviews before buying, or video hosting users check at comments before watching a video. However, not all comments are equally useful. There are a lot of spam comments that do not carry any useful information. The number of spam comments increased especially strongly during a full-scale invasion, when the enemy with the help of bots tries to sow panic and spam the Internet. Very often such comments have different emotional tone than ordinary ones, so it makes sense to use tonality analysis to detect spam comments. The aim of the study is to improve the quality of spam search by doing sentiment analysis (determining the tonality) of comments using machine learning. As a result, an LSTM neural network and a dataset were selected. Three metrics for evaluating the quality of a neural network were described. The original dataset was analyzed and split into training, validation, and test datasets. The neural network was trained on the Google Colab platform using GPUs. As a result, the neural network was able to evaluate the tonality of the comment on a scale from 1 to 5, where the higher the score, the more emotionally positive the text and vice versa. After training, the neural network achieved an accuracy of 76.3% on the test dataset, and the RMSE (root mean squared error) was 0.6478, so the error is by less than one class. With using Naive Bayes classifier without tonality analysis, the accuracy reached 88.3%, while with the text tonality parameter, the accuracy increased to 93.1%. With using Random Forest algorithm without tonality analysis, the accuracy reached 90.8%, while with the text tonality parameter, the accuracy increased to 95.7%. As a result, adding the tonality parameter increased the accuracy for both models. The value of the increase in accuracy is 4.8% for the Naive Bayes classifier and 4.9% for the Random Forest.
Keywords: sentiment analysis; spam detection; neural network; text analyze; Python.